The relationship between technology leadership and teacher ICT competency in higher education - Yuting, Zhang; Adams, Donnie; Lee, Kenny Cheah Soon (Education and information technologies, 2022)
Ever-changing educational technology brings new challenges and opportunities in higher education. To keep up with the trends of the digital era when technology integration is emphasized as one key feature, university leaders should take technology-related responsibilities on motivating and cooperating with teachers to achieve effective technology integration. However, existing explorations mainly discussed the effects of technology leaders on organizational effectiveness or students’ learning outcomes. This study applies descriptive-correlational design to investigate the relationship between university leaders’ and teachers’ technological behaviors and practices. Quantitative data was collected from a Likert questionnaire of 298 teachers in a public university in China and analyzed using descriptive and inferential statistics. The findings indicated a significant direct relationship between technology leadership and teacher ICT competency, all five dimensions of technology leadership showed significant positive effects on teachers. Also, implications and suggestions for current practices and future studies are presented.